TO THE QUESTION OF METHODOLOGICAL ANALYSIS OF THE FINANCIAL CONDITION OF THE ECONOMIC SUBJECT IN MODERN CONDITIONS OF DOING BUSINESS - Schneider, O.V; Izzuka, T.B; Sorokina, V.V (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
Modern business conditions are determined by increased competition, internationalization and globalization of the economy, innovative technological basis and other changes in the financial and economic sphere. The instability of the economic environment is reflected in the level of financial stability of economic entities, which determines the importance of a quick response to changes in the external and internal environment, contributes to the development of measures for effective adaptation to them using an arsenal of the latest management tools and mechanisms. In such a situation, an important aspect of doing business for any economic entity is an effective methodology for analyzing the financial condition of an economic entity, capable of recognizing "sore spots" at an early stage and identifying the risks of financial and economic activity. An effective methodology for analyzing and assessing the financial condition is the most important tool that ensures the stable and effective functioning of an economic entity in modern world space. Along with the possibility of detecting and timely eliminating the negative factors of financial and economic activity, an effective method of analyzing the financial condition provides an assessment of the sustainability of the economic entity and provides an opportunity to identify reserves for increasing the level of financial stability, to determine the risk of possible bankruptcy and helps to develop rational measures for conducting a competitive business. Timeliness of the analysis of the financial condition of an economic entity minimizes the impact of problematic aspects related to financial and economic activities. The problematic aspects of financial and economic activities include: loss of revenue and profit, the occurrence of fines, possible bankruptcy, etc. It should be noted that the sustainability of the economic entity is ensured by a high level of financial condition and economic security, and one of the most reliable indicators of financial condition is to check the organization for the probability of bankruptcy.